2001
DOI: 10.1292/jvms.63.61
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by Enzyme-Linked Immunosorbent Assay and 2-Dimensional Electrophoresis of Haptoglobin in the High-Density Lipoprotein Fraction in Cows.

Abstract: ABSTRACT. Haptoglobin (Hp) is a hemoglobin (Hb)-binding acute-phase protein. Besides its relevance in inflammation, Hp is involved in the regulation of lipid metabolism. In cattle, in addition to the lipoprotein-deficient fraction, Hp is distributed in high-density lipoprotein (HDL) and very high-density lipoprotein (VHDL) fractions. The purpose of this study was to determine Hp concentrations in the lipoprotein fractions using an enzyme-linked immunosorbent assay (ELISA) based on the affinity with Hb, and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…The effect of climatic conditions on haptoglobin in dairy cows is controversial: some authors did not find a season influence on its concentrations (Chan et al 2004), while other authors found higher concentrations in summer than in winter (Wenz et al 2010). It is believed that serum haptoglobin in cows could be involved in the regulation of lipid metabolism (Kanno & Katoh 2001). In our study the patterns of haptoglobin and NEFA were similar among periods.…”
Section: Resultscontrasting
confidence: 52%
“…The effect of climatic conditions on haptoglobin in dairy cows is controversial: some authors did not find a season influence on its concentrations (Chan et al 2004), while other authors found higher concentrations in summer than in winter (Wenz et al 2010). It is believed that serum haptoglobin in cows could be involved in the regulation of lipid metabolism (Kanno & Katoh 2001). In our study the patterns of haptoglobin and NEFA were similar among periods.…”
Section: Resultscontrasting
confidence: 52%
“…Isoelectric point values of Hp in cattle range from 5.05 to 6.28 (Kanno and Katoh 2001), which concurs with the findings of this study. A pI for APOA4 has not been reported, however, and the estimated pI value was 5.51.…”
Section: Proteome Analysissupporting
confidence: 93%
“…In sera from cows with fatty liver, Hp and Hb are detected, in addition to the lipoproteindeficient fraction (d>1.25), in HDL and VHDL fractions [76]. The association of Hp in HDL and VHDL fractions is also found in sera from cows with mastitis [66]. In a calf with hyperlipidemia, Hp, together with apoA-I, was detected in both CM and HDL fractions [193].…”
Section: Apolipoproteinsmentioning
confidence: 93%